PENGARUH POLA DIET DASH TERHADAP TEKANAN DARAH PADA PENDERITA HIPERTENSI : LITERATURE REVIEW THE EFFECT OF THE DASH DIET ON BLOOD PRESSURE IN HYPERTENSION PATIENTS - Vidhiastutik, Yusiana (WELL BEING, 2023)
ABSTRACT Introduction:High blood pressure is a disease that has no specific symptoms and is currently still a global health problem. Dietary changes using the DASH diet can be used in hypertensive patients to control blood pressure to reduce the risk of disease complications due to high blood pressure. Objective: The literature review aims to determine the effect of the DASH diet on blood pressure in people with hypertension. Method:. Search for research journals or literature studies on the pages of "Google Scholar, PubMed, Science Direct and Springer" published from 2018 to 2023, and then select, analyze and review the obtained articles according to the topic. Finally, compile the results of the review from multiple sources. Results: The DASH diet has been shown to effectively reduce blood pressure in hypertensive patients, both adults and the elderly. The DASH diet is based on the principles of eating low in sodium, high in fiber, calcium, potassium, magnesium and fiber, and limiting saturated fat and cholesterol. Conclusion: The DASH diet pattern can be used to control blood pressure in hypertensive patients. Suggestion: Hypertension patients can adopt a healthy lifestyle to control blood pressure by implementing the DASH diet pattern. Keywords: Family income, Events below the red line (BGM). Small child